Structural Properties of Prepared PANI/TiO2 Nanocomposite by Chemical Polymerization - Abid, Noor K.; Salma M. Hasan (Iraqi Journal of Physics, 2022)
A progression of Polyaniline (PANI) and Titanium dioxide (TiO2) nanoparticles (NPs) were prepared by an in-situ polymerization strategy within the sight of TiO2 NPs. The subsequent nanocomposites were analyzed using Fourier-transform infrared spectra (FTIR), X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and Energy Dispersive X-Ray Analysis (EDX) taken for the prepared samples. PANI/TiO2 nanocomposites were prepared by various compound materials (with H2SO4 0.3 M and without it, to compare the outcome of it) by the compound oxidation technique using ammonium persulfate (APS) as oxidant within the sight of ultrafine grade powder of TiO2 cooled in an ice bath. Nanocomposites were prepared by the addition of TiO2 with two weight ratios (0.3 and 0.5 wt. %) during the polymerization of PANI. The outcomes showed good collaboration between PANI and TiO2. FTIR spectral shows a shift to higher wave numbers in the peaks of PANI/TiO2 nanocomposites, due to the Coulomb force that resulted from the interaction between the TiO2 nanoparticles with PANI. SEM results show that the TiO2 nanoparticles enwrap the polyaniline and agglomeration of uneven distribution of TiO2 particles can be seen in the PANI matrix. The intensity of the peak in the EDX analyses was found to appear by adding the nanoparticles. XRD pattern of PANI polymerization and PANITNCs shows that the TiO2 NPs and PANI affected the crystallization performance of nanocomposites, it was identified that the TiO2 NPs form a relatively irregular distribution in the PANI chain.